Elementos filosóficos do conceito de Direitos Humanos - Pangoni, Rafael (2024)
This thesis attempts to understand the philosophical elements of universal human rights. By using the historical and contextual method, it addresses how philosophy has shaped contemporary international human rights law. The three main topics are the human being as such, universality, and natural law. Cicero and the Stoics studied the human being outside the polis, universal unwritten law and the idea of Cosmopolis, laying the foundations for the development of the ius gentium. St Paul, the Apostle to the Gentiles, picked the idea of universalism and developed it with a sense of religiosity; the Church Fathers and, in the Middle Ages, St Thomas Aquinas, in their theological studies, developed the idea of person. In the Renaissance, Francisco de Vitoria, in his defence of the indigenous peoples, carried out the two “relectiones de indis”, founding international law and establishing a sophisticated idea of human dignity, inspired by Stoicism and Scholasticism. Later, during the Modern era, John Locke raised his voice against the patriarchal absolutism of Robert Filmer, raising disputes that would lead back to the thought of John of Salisbury and developing ideas about human rights. After the Second World War, there was a return to universality: the issues of human nature were reintroduced by Charles Malik during the drafting of the Universal Declaration of Human Rights. However, without a profound common reference, the paradigm of human rights—and consequently of humanitarian law and refugee law—took on a positivistic and specifies form, so as to create antinomies that are difficult to harmonise. This problem may be addressed with Jacques Maritain’s idea of connatural knowledge of natural law